PERAN LITERASI KEUANGAN DAN PERILAKU KEUANGAN UNTUK MENINGKATKAN MINAT INVESTASI MAHASISWA - Muhammad Nur Fietroh; Baiq Sarah Andriani (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This study aims to examine the effect of financial literacy and financial behavior on investment interest. This study uses quantitative methods with a sample of 100 respondents. With the sampling technique using simple random sampling method. The data collection method was carried out by distributing questionnaires online via google form. This study uses multiple linear regression analysis techniques using the help of the Statistical Package for Social Science (SPSS). The results of the analysis in this study indicate that (1) the financial literacy variable has a partial and significant effect on investment interest. (2) The financial behavior variable has a partial and significant effect on investment interest.